Recurrent IPDA Aneurysm from Celiac Occlusion Treated by a Flow Diverting Stent - Kumari, Divya; Funaki, Brian (Journal of Clinical Interventional Radiology ISVIR, 2022)
Inferior pancreaticoduodenal artery (IPDA) aneurysms have been associated with celiac axis stenosis and occlusion. Retrograde flow through the IPDA arcade has been hypothesized to cause enlargement of these vessels and lead to aneurysm formation. However, objective proof of this hypothesis is lacking, given the fact that celiac stenosis or occlusion and IPDA aneurysms are typically diagnosed concurrently and recurrent aneurysms have not been described. This report presents a patient with celiac axis stenosis and an IPDA aneurysm treated with median arcuate ligament lysis, celiac stenting, and aneurysmectomy. Seventeen years later, he developed a second IPDA aneurysm treated with a flow diverting stent.
Keywords: mesenteric aneurysm; celiac stenosis; flow diverting stent